Renewing rail infrastructure management by developing a cost calculation methodology based on ABC - Hokstok, Csaba (Periodica Polytechnica Transportation Engineering, 2011)
Due to liberalisation the structure of the rail transport sector - including rail infrastructure management - is changing significantly. Beside technological innovations the improvement of the accounting system has also had a marginal role in the rail development process. The aim of the study is to create a new cost calculation method for rail infrastructure management on the basis of Activity Based Costing (ABC). To reach this target it is necessary to analyse the activities of the Hungarian incumbent rail company. A critical stage in this process is to identify the cost drivers based on real rail performances through the definition of the cause-effect relations between infrastructure management activities and infrastructure services. Using this new model yields more accurate rail infrastructure costs on the one hand while costs based on more exact calculations can lead to more realistic determination of the user charges on the other hand.